Power, Gender and Politics: Forms of Control and Ecofeminist Resistance in The Handmaid’s Tale - Cesaro , Laura; Riva, Claudio (Funes. Journal of narratives and social sciences, 2024)
Set in the totalitarian society of Gilead, The Handmaid’s Tale (2017 – ongoing) meticulously explores the intersection of power, gender and politics. Through the lens of protagonist Offred, viewers witness the systematic erosion of individual rights and freedoms in the name of societal order: echoing themes of authoritarianism, misogyny and resistance. In relation with the latter, the authors use surveillance studies to analyse political control practices and employ the lens of ecofeminism to read the handmaids’ collective action. The article highlights how the TV series serves as a poignant commentary on contemporary political discourse. Through its vivid portrayal of dystopia, the TV series underscores the imperative of political vigilance and collective action in safeguarding human rights and civil liberties. As viewers confront the harsh realities of Gilead, they are compelled to recognise parallels and implications within their own socio-political contexts, thereby igniting discourse and advocacy for a more just and equitable world.